1999
DOI: 10.1159/000029099
|View full text |Cite
|
Sign up to set email alerts
|

Non-Right-Handedness and Obstetrical Complications in Paranoid Hallucinatory Schizophrenics

Abstract: In previous studies a link between pregnancy complications, minor physical anomalies and non-right-handedness was described in schizophrenic patients. There is evidence of an anomaly in the lateralization process in schizophrenia. Many studies of handedness and schizophrenia have found that schizophrenic patients have an increased rate of non-right-handedness compared with normal subjects. The contemporary neurodevelopmental hypothesis of schizophrenia emerged from pathobiological findings. In addition there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 42 publications
1
11
2
Order By: Relevance
“…This finding is in contrast with those of some studies that have found no gender differences in relation to handedness in schizophrenia whereas several authors have found an association between non-right handedness and the male gender [11][12][13][14][15] . Our study found no association between age at onset of illness and handedness in schizophrenia/ schizoaffective disorder.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding is in contrast with those of some studies that have found no gender differences in relation to handedness in schizophrenia whereas several authors have found an association between non-right handedness and the male gender [11][12][13][14][15] . Our study found no association between age at onset of illness and handedness in schizophrenia/ schizoaffective disorder.…”
Section: Discussioncontrasting
confidence: 99%
“…The relationship between gender, atypical handedness and schizophrenia has also been studied but the results are inconsistent. Some studies have found no gender differences in relation to handedness in schizophrenia whereas several authors have found an association between non-right handedness and the male gender [10][11][12][13][14][15] . In contrast, a study by Kenneth et al showed that patients with schizophrenia and their mentally well relatives had an excess of mixed handedness compared to controls, and this excess was specific to female patients suffering from schizophrenia.…”
Section: Journal Of Psychiatry • January 2014mentioning
confidence: 99%
“…left–mixed–right, as in Table 2), being entirely based on assessment of multiple manual activities using either self‐report or demonstration. Six studies (20, 25–29) used the ‘right’ vs. ‘non‐right’ classification (i.e. combining both left‐ and mixed‐handers together), and six studies (11, 12, 15, 19, 30, 31) used the ‘mixed’ vs. ‘non‐mixed’ classification (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…While the scoring of handedness varied in strictness between articles, each article presented frequencies for abnormal (all versions of non-right) handedness, which allowed for the comparison of percent abnormal between diagnostic groups between studies. A total of 16 articles fulfilled our selection criteria, with some articles reporting data for multiple handedness categories (3 non-right: O’Callaghan et al, 1995; Sperling et al, 1999; Yan et al, 1985; and 11 left: Clementz, Iacono et al, 1994; Dragovic and Hammond, 2005; Egan, Hyde et al, 2001; Green, Satz, Smith et al, 1989; Lawrie et al, 1999a; Malesu et al, 1996; Nelson et al, 1993; Reilly et al, 2001; Shapleske et al, 2001; Taylor and Abrams, 1984; Upadhyay et al, 2004; and 10 mixed: Dragovic and Hammond, 2005; Egan, Hyde et al, 2001; Giotakos, 2001; Green, Satz, Smith et al, 1989; Gureje, 1988; Malesu et al, 1996; Nelson et al, 1993; Reilly et al, 2001; Taylor and Abrams, 1984; Upadhyay et al, 2004). Percent abnormal calculations are presented in Table 3.…”
Section: Neuromotor Abnormalitiesmentioning
confidence: 99%